Caracterização físico-quimica e avaliação de biocompatibilidade de biovidros estudo laboratorial e histomorfométrico em ratos - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2004)
The purpose of this study was to evaluate physic-chemical characteristics and the biocompatibility of the bioglass, developed by the UEPG Chemistry Department, (UEPG Bioglass) and compare it with the PerioGlas® e Biogran®. The physicchemical characterization was made by scanning electron microscopy (SEM) (size and morphology of particles); scanning electron microscopy/energy dispersive X Ray (MEV/EDAX) (chemical elements); X Ray diffractometry (DRX) (structure); X Ray fluorescence (FRX) (chemical elements) For the biocompatibility test was used 100 rats: Gl-PerioGlas® - 25 animals; Gll – Biogran® - 25 animals; Glll – Biovidro UEPG – 25 animals; GIV – Control (surgical procedure without implantation of biomaterial) – 25 animals. The animals were evaluated at 7, 15, 21, 45 and 60 days. It was used histomorphometric analysis to determine the size of inflammatory reaction, size of granules, the presence and quantity of polymorphonuclear cells (PMN), mononuclear (MN) and fibroblast (F). The results shown that the particles of the three materials were irregular with superficial roughness. The medial size of PerioGlas® granules was 222,00±40,64 µm. The Biogran® granules with 385.09±68.51µm. And the UEPG Bioglass was 102.86±36.22µm. There was significant difference in the size of granules (p<0.001-ANOVA). The three samples presented calcium, oxygen, sodium, phosphorus and silica, aggregated on silica oxide, sodium oxide, calcium oxide and phosphorus oxide. The materials were no crystalline and with crystalline points in their surfaces. There was significant difference on size of inflammatory reaction between groups, times and interaction (group*time) (p<0.001). There was not significant difference between on the count of MN between groups (p=0.117), there was difference between times (p<0.001) and interaction (p=0.022). There was significant difference (p<0.001) on the count of PMN between the times, groups and interaction. There was not significant difference on the count of F between the groups (p=0.131) and interaction (p=0.665), with significant difference between the times (p=0.008). There was significant difference on granules size between the groups, time and interaction (p<0.001). It was concluded that the three materials were biocompatible and bioreabsorbable, without sign of osteoinducture capacity.
Keywords: materiais biocompatíveis; vidro; substitutos ósseos; biocompatible materials; glass; bone substitutes; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA